About 335 nm Ultraviolet Emissions Obtained from Simple Metal–Insulator–Semiconductor Light‐Emitting Tunnel Diodes. Issue 2 (25th November 2020) - Lin, Chen-Sheng; Allsopp, Duncan W. E.; Cavanagh, Kate; Tsui, Hei Chit Leo; Yu, Ling-Shan; Wang, Wang-Nan; Mihai, Andrei; Zou, Bin; Moram, Michelle A.
Abstract : To overcome the low external quantum efficiency of ultraviolet light‐emitting diodes (UV LEDs) in the technologically significant wavelength range of 300–350 nm, a change of approach to device design may be required. Herein, room‐temperature electroluminescence (EL) at 335 nm is achieved from simple aluminum gallium nitride (AlGaN)‐based metal–insulator–semiconductor (MIS) light‐emitting diodes (LEDs), which do not contain any p‐doped material. Current–voltage and capacitance–voltage measurements indicate that electrons in the valence band of the n‐Al0.14 Ga0.86  N layer efficiently tunnel via localized states in the thin, sputter‐deposited aluminum nitride (AlN) barrier of the MIS device to provide the source of holes needed for near‐band‐edge luminescence. The full width at half maximum (FWHM) in the UV emission peak is only around 18 nm and it is very close to the photoluminescence (PL) peak of the active n‐Al0.14 Ga0.86 N layer, confirming that the EL is derived from band‐to‐band radiative transitions in the simple non‐p‐doped MIS diode. This design is a potential option to overcome the problem of the poor thermal excitation of holes in the AlGaN‐based pn junction devices. Abstract : Room‐temperature electroluminescence at 335 nm is achieved from simple aluminum gallium nitride‐based metal–insulator–semiconductor light‐emitting diodes. Current–voltage and capacitance–voltage measurements indicate that electrons in the valence band of the n‐Al0.14 Ga0.86 N layer efficiently tunnel via localized states in the thin, sputter‐deposited aluminum nitride barrier of the device to provide the source of holes needed for near‐band‐edge luminescence.